Lesartenbündel zur Vignette `Dann musst du mal über Strategien nachdenken!´ - Reis, Oliver (Inklusion verstehen. Szenen aus dem Unterricht in interdisziplinärer Reflexion)

Eine praxistheoretische Lesart gegen den inklusionspädagogischen Strich - Reis, Oliver (Inklusion verstehen. Szenen aus dem Unterricht in interdisziplinärer Reflexion)

Eine praxistheoretische Lesart zu Expertinnen- und Expertenrollen - Reis, Oliver (Inklusion verstehen. Szenen aus dem Unterricht in interdisziplinärer Reflexion)

Eine praxistheoretische Lesart zur Rolle der Schulbegleitung - Reis, Oliver (Inklusion verstehen. Szenen aus dem Unterricht in interdisziplinärer Reflexion)

Eine praxistheoretische Lesart zum Erkunden - Reis, Oliver (Inklusion verstehen. Szenen aus dem Unterricht in interdisziplinärer Reflexion)

Religion und Freiheit - Süßmann, Johannes

Gabriel, der Gesandte Gottes – Überlegungen über Surat at-takwīr (Koransure 81) - Abdelrahem, Mohammed

Zentrale Regulierungs- und Aufsichtsnormen für Bankrisiken - Uhde, André (Bankpolitik - Eine marktorientierte Einführung)

Bankpolitik - Eine marktorientierte Einführung

Plurikulturelle digitale DaF-Lehrkompetenzen im Fokus - Prikoszovits, Matthias (KONTEXTE: Internationales Journal zur Professionalisierung in Deutsch als Fremdsprache)

Symplectic Methods in Deep Learning - Maslovskaya, Sofya; Ober-Blöbaum, Sina (IFAC-PapersOnLine)

Inverse optimal control problem in the non autonomous linear-quadratic case - Jean, Frédéric; Maslovskaya, Sofya

ICILS 2023 #NRW. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen in Nordrhein-Westfalen im internationalen Vergleich - Drossel, Kerstin; Eickelmann, Birgit; Niemann, Jan; Niggemeier, Johannes Bernd

Siebter Oktober Dreiundzwanzig. Antizionismus und Identitätspolitik

An approach for a metamodel-based consideration of a process chain when mechanically joining sheet metal components - Neumann, Jonas; Kappis, Lukas; Lontsi, Seraphin Tsi-Nda; Ludwig, Jean-Patrick; Ramaiya, Umang Bharatkumar; Scharr, Christian; Vallaster, Eva; Flügge, Wilko; Meschut, Gerson; Merklein, Marion (15th Forming Technology Forum)
Batch and process fluctuations during the fabrication of sheet metal components result in discrepancies in the resulting component properties, affecting subsequent process steps and potentially leading to production rejects. Consequently, the identification of deviations and knowledge of the effects of fluctuations are crucial for achieving consistently high product quality, reducing waste and thus increasing resource efficiency of production processes through countermeasures derived from this. The approach presented to address this is the use of data-driven metamodeling to map entire process chains and predict process parameters in order to compensate for process and batch fluctuation. The investigated process chain consists of the sub-processes deep drawing, clamping and clinching. For each process step, relevant input and output variables are identified, numerical simulation models are created, and subsequently validated. Variant simulations of the sub-processes are conducted and evaluated to generate a database for the metamodeling of the individual process steps. Machine learning techniques are utilized for the automated selection and optimization of learning methods to create models that depict the relationships between input and output variables. Finally, the models for the sub-processes are linked together to form a superordinate metamodel for the entire process chain, with the aim to make inline-process adaptations possible.<br

Parameterized complexity of weighted team definability - Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Vollmer, Heribert (Mathematical Structures in Computer Science)
Abstract In this article, we study the complexity of weighted team definability for logics with team semantics. This problem is a natural analog of one of the most studied problems in parameterized complexity, the notion of weighted Fagin-definability, which is formulated in terms of satisfaction of first-order formulas with free relation variables. We focus on the parameterized complexity of weighted team definability for a fixed formula $φ$ of central team-based logics. Given a first-order structure $\mathcal{A}$ and the parameter value $k\in \mathbb N$ as input, the question is to determine whether $\mathcal{A},T\models φ$ for some team T of size k . We show several results on the complexity of this problem for dependence, independence, and inclusion logic formulas. Moreover, we also relate the complexity of weighted team definability to the complexity classes in the well-known W-hierarchy as well as paraNP.

Die Pflicht, up-to-date zu sein. Adressierungen (werdender) Eltern durch Schwangerschafts- und Erziehungsapps - Sänger, Eva; Langer, Antje; Carstensen, Tanja (GENDER – Zeitschrift für Geschlecht, Kultur und Gesellschaft)
Software-Apps sind inzwischen zentraler Bestandteil des alltäglichen Lebens. Vor dem Hintergrund dieser umfassenden Digitalisierung des Sozialen fragt der Beitrag danach, welche Selbstverhältnisse und generationalen Beziehungen durch Erziehungs- und Schwangerschaftsapps konstruiert und adressiert werden, welche normierenden Effekte diese Apps haben und welche Themen ausgeklammert werden. Der Beitrag beruht auf einer qualitativen Analyse von 55 Inhaltsbeschreibungen von Schwangerschafts- und Erziehungsapps aus App-Stores. Wir zeigen, dass neben hetero- und geschlechternormativen Adressierungen Schwangere und Eltern als vorausschauende Subjekte adressiert werden, die im Sinne einer antizipatorischen Risikologik insbesondere mit einem Regime des Upto- Date- bzw. Alert-sein-Müssens und einer ‚Pflicht zum Wissen‘ konfrontiert sind. Der Handlungsdruck, der auf diese Weise erzeugt wird, geht zugleich mit dem Versprechen einher, diese Aufgaben an die App abgeben zu können.

Covariational reasoning in Bayesian situations - Büchter, Theresa; Eichler, Andreas; Böcherer-Linder, Katharina; Vogel, Markus; Binder, Karin; Krauss, Stefan; Steib, Nicole (Educational Studies in Mathematics)
Abstract Previous studies on Bayesian situations, in which probabilistic information is used to update the probability of a hypothesis, have often focused on the calculation of a posterior probability. We argue that for an in-depth understanding of Bayesian situations, it is (apart from mere calculation) also necessary to be able to evaluate the effect of changes of parameters in the Bayesian situation and the consequences, e.g., for the posterior probability. Thus, by understanding Bayes’ formula as a function, the concept of covariation is introduced as an extension of conventional Bayesian reasoning, and covariational reasoning in Bayesian situations is studied. Prospective teachers ( N =173) for primary ( N =112) and secondary ( N =61) school from two German universities participated in the study and reasoned about covariation in Bayesian situations. In a mixed-methods approach, firstly, the elaborateness of prospective teachers’ covariational reasoning is assessed by analysing the arguments qualitatively, using an adaption of the Structure of Observed Learning Outcome (SOLO) taxonomy. Secondly, the influence of possibly supportive variables on covariational reasoning is analysed quantitatively by checking whether (i) the changed parameter in the Bayesian situation (false-positive rate, true-positive rate or base rate), (ii) the visualisation depicting the Bayesian situation (double-tree vs. unit square) or (iii) the calculation (correct or incorrect) influences the SOLO level. The results show that among these three variables, only the changed parameter seems to influence the covariational reasoning. Implications are discussed.

How to teach Bayesian reasoning: An empirical study comparing four different probability training courses - Steib, Nicole; Büchter, Theresa; Eichler, Andreas; Binder, Karin; Krauss, Stefan; Böcherer-Linder, Katharina; Vogel, Markus; Hilbert, Sven (Learning and Instruction)

Frauenemanzipation in islamischen Ländern. Vom 19. Jahrhundert bis in die Gegenwart (Ariadne. Forum für Frauen- und Geschlechtergeschichte)